Associations between genetically determined dietary factors and risk of autism spectrum disorder: a Mendelian randomization study - Li, Wenwen; Liu, Cuncheng; Chen, Shouqiang (Frontiers in Nutrition, 2024)
Background: Existing studies confirm the importance of dietary factors in developing autism spectrum disorder (ASD) and disease progression. Still, these studies are primarily observational, and their causal relationship is unknown. Moreover, due to the extensive diversity of food types, the existing research remains somewhat limited in comprehensiveness. The inconsistency of the results of some studies is very disruptive to the clinic. This study infers a causal relationship between dietary factors on the risk of developing ASD from a genetic perspective, which may lead to significant low-cost benefits for children with ASD once the specificity of dietary factors interfering with ASD is confirmed.We performed a two-sample Mendelian randomization (MR) analysis by selecting single nucleotide polymorphisms (SNPs) for 18 common dietary factors from the genome-wide association study (GWAS) database as instrumental variables (IVs) and obtaining pooled data for ASD (Sample size=46,351) from the iPSYCH-PGC institution.Inverse variance weighted (IVW) was used as the primary analytical method to estimate causality, Cochran's Q test to assess heterogeneity, the Egger-intercept test to test for pleiotropy and sensitivity analysis to verify the reliability of causal association results.The MR analysis identified four dietary factors with potential causal relationships: poultry intake (fixed-effects IVW: OR=0.245, 95%CI: 0.084-0.718, P<0.05), beef intake (fixed-effects IVW: OR=0.380, 95%CI: 0.165-0.874, P<0.05), cheese intake (random-effects IVW: OR=1.526, 95%CI: 1.003-2.321, P<0.05), and dried fruit intake (fixed-effects IVW: OR=2.167, 95%CI: 1.342-3.501, P<0.05). There was no causal relationship between the remaining 14 dietary factors and ASD (P>0.05).This study revealed potential causal relationships between poultry intake, beef intake, cheese intake, dried fruit intake, and ASD. Poultry and beef intake were associated with a reduced risk of ASD, while cheese and dried fruit intake were associated with an increased risk. Other dietary factors included in this study were not associated with ASD.